PEMBERIAN EKSTRAK MORINGA OLEIFERA SEBAGAI UPAYA PREVENTIF KEJADIAN STUNTING PADA BALITA - Dyah Muliawati; Nining Sulistyawati (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Patterns of height growth and weight reflect the status of nutrients and health conditions. RISKESDAS results (2018) showed that the proportion of short (stunting) toddlers increased from 19.2% in 2013 to 19.3% at 2018. The purpose of the research is to know the benefits of Moringa Oleifera extract in increasing the toddler's height. The type of research used is experimental quasi, hypothesis test using Pearson Product Moment correlation, and multivariate analysis using multiple linear regression. Location of research in the working area of Piyungan Puskesmas. The number of samples of each 45 respondents in the treatment and control group was taken in purposive sampling. Data collection tools with questionnaires and height measurements of toddlers. The results showed that Moringa Oleifera extract could increase body height by 0.342 cm with a prediction of 16.2%; Maternal education can increase the toddler's height by 0.476 cm with a prediction of 34.1%; Mother's education and maternal work can increase the toddler's height by 0.594 cm with a prediction of 27.9%; Mother's education, maternal work and number of family members can increase their height by 0.528 cm with a prediction of 19.6%; Mother's education, maternal work, number of family members and protein intake can increase the toddler's height by 0.528 cm with a prediction of 12.6%.